Zagadnienie Płyty Siatkowej Obciążonej w Węzłach i Między Węzłami - J. Lewiński (Engineering Transactions, 2015)
The paper presents the problem of a lattice plate which is loaded both at the nodes and between the nodal points, at an arbitrary number of intermediate points of the beam elements. Under such loading conditions, the state of stress and displacement is described, physical relations are given, and the equations of equilibrium are derived in terms of displacements. Moreover, presented is the method of solution of the boundary value problem as also the method of solution of the equilibrium equations derived. The paper is illustrated by a particular example.